Alternatively spliced short and long isoforms of adaptor protein intersectin 1 form complexes in mammalian cells - Gubar, O.S.; Kropyvko, S.V.; Tsyba, L.O.; Gasman, S.; Rynditch, A.V. (Вiopolymers and Cell, 2012)
Intersectin 1 (ITSN1) is an adaptor protein involved in membrane trafficking and cell signaling. Long and short isoforms of ITSN1 (ITSN1-L and ITSN1-S) are produced by alternative splicing. The aim of our study was to investigate whether ITSN1-L and ITSN1-S could interact in mammalian cells. Methods. During this study we employed immunoprecipitation and confocal microscopy. Results. We have shown that endogenous ITSN1-S coprecipitates with overexpressed ITSN1-L in PC12, 293 and 293T cells. Long and short isoforms of ITSN1 also colocalize in 293T cells. Conclusions. ITSN1-L and ITSN1-S form complexes in mammalian cells. Keywords: ITSN1, alternatively spliced isoforms, adaptor/scaffold proteins.